10 Knockdown of transforming growth factor beta regulator 4 (tbrg4) promotes apoptosis in human lung cancer cell line h1299 via regulating ddit3, cav1 and rrm2. (5th December 2017) - Wang, Ansheng; Liu, Xuegang; Su, Wen; Duan, Guixin; Xie, Zongyu; Chu, Shanshan
Abstract: Transforming growth factor beta regulator 4 (TBRG4) gene is located on 7 p14-p13, a region correlated with many cancer types, such as hematologic malignancies, head and neck squamous cell carcinoma, and multiple myeloma. However, the role of TBRG4 in human lung cancer is largely unknown. Thus, in the present study, the TBRG4 mRNA level was evaluated in the lung cancer cell line H1299 by quantitative PCR (qPCR) after knocking down TBRG4 using lentivirus-mediated small interfering RNA (siRNA). The result showed that TBRG4 was significantly inhibited in H1299 by RNAi. Microarray analysis revealed 586 differentially-expressed genes after TBRG4 silencing. Analysis of the dataset with differentially-expressed genes using Ingenuity Pathway Analysis (IPA) software showed that infectious diseases, cancer, organismal injury and abnormalities were functions associated with the highest rated network. Further analysis of this network by IPA revealed that TBRG4 knockdown in H1299 cells changed the levels of downstream genes, including the upregulation of DDIT3 and downregulation of CAV1 and RRM2. These results have been validated by qPCR and Western blotting. Moreover, TBRG4 was shown to be highly expressed in carcinoma by immunohistochemstry compared with adjacent carcinomatous normal tissue. However, there were no associations between TBRG4 expression and clinicopathological characteristic, including sex, age, distant metastasis, TNM stage, and tumour grade. Taken together, TBRG4 plays an anti-apoptotic role in tumorigenesis of lung cancer via regulating DDIT3, CAV1 and RRM2 expression. The present findings are potentially significant to advance the understanding of TBRG4 as a candidate for the treatment of lung cancer.